Pengembangan Media Pembelajaran Komik Digital Berbasis Canva pada Materi Kearifan Budaya Lokal di Kelas 4 SDN 1 Tawing Kecamatan Gondang Kabupaten Tulungagung: Penelitian - Isfaringga Aysya; Jannataka Nugrananda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aimed to develop and test the feasibility and applicability of Canva-assisted Digital Comic learning media for Local Wisdom material for 4th-grade students at SDN 1 Tawing, given the limited use of innovative media and the dominance of conventional methods that lead to low student motivation. Employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation), data were collected through questionnaires, interviews, and documentation. Validation results indicated that this media is highly valid, with media experts rating it 84% and material experts 94%. The media's applicability was also very high, evidenced by student responses in small groups (93%) and large groups (94%), both falling into the